THE EFFECT OF RETURN ON ASSETS, RETURN ON EQUITY AND NET INTEREST MARGIN ON STOCK PRICES IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Widyakto, Adhi; Rinawati, Tri; Widyarti, Endang Tri (JURNAL BISNIS STRATEGI, 2023)
This research was conducted to test the effect of the variable Return On Asset (ROA) Return On Equity (ROE) Net Interest Margin (NIM) on stock prices in banking companies listed on the Indonesian stock exchange for the 2017-2021 period. The data used in this writing is obtained from financial statement data published by idx taken from the www.idx.co.id website. This study used quantitative data with multiple linear regression techniques. The sample of this study was determined by purposive sampling technique and produced 13 company samples for analysis.The results of this study show that Return On Asset (ROA) has a significant effect on the share price of banks listed on the Indonesia Stock Exchange, Return On Equity (ROE) does not have a significant effect on the share price of banks listed on the Indonesia Stock Exchange, Net Interest Margin (NIM) has a significant effect on the stock prices of banks listed on the Indonesia Stock Exchange.